1993
DOI: 10.1021/j100145a003
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of hydroxyl radical reactions with methane and perdeuterated methane

Abstract: We measured absolute rate coefficients for the reactions of the hydroxyl radical with methane (kl) and methaned4 (k2) using the laser photolysis/laser-induced fluorescence technique. We characterized kl and k2 over the temperature range 293-800 K at pressures between 400 and 750 Torr of helium. We find excellent agreement between our results and the recent determinations of kl at lower temperatures by Vaghjiani and Ravishankara.The measured rate coefficients, in the units cm3 molecule-' s-l, fit well to the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 2 publications
11
79
0
1
Order By: Relevance
“…The recent studies of Bott and Cohen (1989), Vaghjiani and Ravishankara (1991), Finlayson-Pitts et al (1992), Lancar et al (1992), Dunlop and Tully (1993), Mellouki et al (1994), Gierczak et al (1997) and Bonard et al (2002) are in good agreement, as shown by the Arrhenius plot in Fig. 1.…”
Section: Oh+methanesupporting
confidence: 70%
See 2 more Smart Citations
“…The recent studies of Bott and Cohen (1989), Vaghjiani and Ravishankara (1991), Finlayson-Pitts et al (1992), Lancar et al (1992), Dunlop and Tully (1993), Mellouki et al (1994), Gierczak et al (1997) and Bonard et al (2002) are in good agreement, as shown by the Arrhenius plot in Fig. 1.…”
Section: Oh+methanesupporting
confidence: 70%
“…This rate expression is plotted as the solid line in the Arrhenius plot ( Fig. 1), and provides an excellent fit to the data of Bott and Cohen (1989), Vaghjiani and Ravishankara (1991), Finlayson-Pitts et al (1992), Lancar et al (1992), Dunlop and Tully (1993), Mellouki et al (1994), Gierczak et al (1997) and Bonard et al (2002), agreeing with the 1234 K rate constant of Bott and Cohen (1989) to within 1% and with the 800 K rate constant of Dunlop and Tully (1993) and the 295-668 K rate constants of Bonard et al (2002) to within 10%. Accordingly, the rate expression of Gierczak et al (1997) The overall uncertainty in the rate constant at 298 K is estimated to be ±20%.…”
Section: Oh+methanementioning
confidence: 60%
See 1 more Smart Citation
“…Substitution of hydrogen for deuterium in direct abstraction reactions typically results in significant kinetic isotope effects. Measured kinetic isotope effects for hydrogen abstraction by ·OH range from 2.0 to 6.8 and decrease linearly with temperature [34]. Thus, monitoring deu- terium transfers provides a lower limit to the extent of hydrogen transfers that would occur in an unlabeled peptide.…”
Section: Resultsmentioning
confidence: 99%
“…The resultant OH radicals are highly reactive such that they are able to abstract hydrogen from methane [19]. The methyl radicals thus formed are then able to couple to form ethane.…”
Section: Resultsmentioning
confidence: 99%